Pembentukan Karakter Disiplin Peserta Didik Yang Berbasis Kemaritiman Melalui Kepemimpinan Multikultural - Dewi Sartika; Sitti Hartinah; Taufiqulloh (Universitas Pancasakti Tegal, 2020)
This study aims to create a maritime-based disciplinary character for students through multicultural leadership at SMK SUPMYamipura Suradadi, Tegal Regency. The population and sample of this study were 30 students. The research method used in thisresearch is quantitative quantitative analysis. Collecting data in this study using documentation and questionnaires. The data analysisthat the writer uses is the proportional descriptive analysis technique and the t-test. The results showed that the disciplinary characterof students before implementing multicultural leadership at SMK SUPM Yamipura Suradadi Tegal Regency was in the low criteriaof 8 students (26.7%). While the disciplinary character of students after implementing multicultural leadership at SMK SUPMYamipura Suradadi, Tegal Regency, is a high criterion of 12 students (40.0%). Multicultural Character formation is carried out inschools by utilizing school culture including: school artifacts, school ceremonies, school rules, values and beliefs. MulticulturalCharacter Building is carried out in schools by utilizing school culture. School culture has a role in producing good work productivityfor each individual and school work unit. From the results of the analysis, it was obtained the t-count value of 5.63. The tcount value isthen consulted with t table at a significant level of 5% or ( 5%) with degrees of freedom N-1 or 30 - 1 = 29 where t table = 2.042 turnsout that tcount = 5.63> t table = 2.042 which means that the null hypothesis is rejected. and accepting the hypothesis that reads